Governance in the Health Sector : A Strategy for Measuring Determinants and Performance - Savedoff, William D. (2012)
Many different strategies have been proposed to improve the delivery of health care services, from capacity building to establishing new payment mechanisms. Recent attention has also asked whether improvements in the way health care services are governed could make a difference. These approaches ask which factors -- such as rules and institutions -- influence the behavior of the system in ways that are associated with better performance and outcomes. This paper reviews the concept of governance as it is used in the literature on private firms, public administration, international development and health. It distinguishes between indicators that measure governance determinants from those that measure governance performance in order to propose a framework that is analytically coherent and empirically useful. The framework shows how these indicators can be used to test hypotheses about which governance forms are more useful for improving health system performance. The paper concludes by proposing specific measures of governance determinants and performance and describes the instruments available to collect and interpret them.